2023
DOI: 10.3390/geosciences13070212
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal and Analysis of Macroseismic Data for Seismotectonic Purposes: The Strong Earthquakes of Southern Calabria, Italy

Abstract: In tectonically active areas, such as the Italian peninsula, studying the faults responsible for strong earthquakes is often challenging, especially when the earthquakes occurred in historical times. In such cases, geoscientists need to integrate all the available information from historical reports, surface geology, and geophysics to constrain the faults responsible for the earthquakes from a seismotectonic point of view. In this paper, we update and review, according to the EMS-98 scale, the macroseismic fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 128 publications
(251 reference statements)
2
3
0
Order By: Relevance
“…Adopting a multidisciplinary approach based on morphostructural field data integrated with seismological and geodetic data, we modelled the 3D geometry of the Cittanova and Serre faults in southern Calabria, performed the FRM simulation for these faults, and evaluated their propensity to slip in the MOVE environment. On the basis of our results (maximum expected magnitude, vertical slip evaluation, and slip tendency) and according to the historical report (de Dolomieu ( 1784)) and previous works (Jacques et al, 2001;Andrenacci et al, 2023), we found that CF and SRF (called "debated seismogenic sources" in DISS; DISS Working Group, 2021, https://diss.ingv.it/) are the best candidate sources of the 5 February, 7 February, and 1 March 1783 events. On the contrary, the Gioia Tauro and Mesima faults do not exhibit surface evidence (e.g., coseismic scarplet, cumulative morphological scarps, kinematic indicators, and tectonic control on the drainage network) that would testify a recent activity associated with them.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Adopting a multidisciplinary approach based on morphostructural field data integrated with seismological and geodetic data, we modelled the 3D geometry of the Cittanova and Serre faults in southern Calabria, performed the FRM simulation for these faults, and evaluated their propensity to slip in the MOVE environment. On the basis of our results (maximum expected magnitude, vertical slip evaluation, and slip tendency) and according to the historical report (de Dolomieu ( 1784)) and previous works (Jacques et al, 2001;Andrenacci et al, 2023), we found that CF and SRF (called "debated seismogenic sources" in DISS; DISS Working Group, 2021, https://diss.ingv.it/) are the best candidate sources of the 5 February, 7 February, and 1 March 1783 events. On the contrary, the Gioia Tauro and Mesima faults do not exhibit surface evidence (e.g., coseismic scarplet, cumulative morphological scarps, kinematic indicators, and tectonic control on the drainage network) that would testify a recent activity associated with them.…”
Section: Discussionsupporting
confidence: 74%
“…Frontiers in Earth Science frontiersin.org Jacques et al, 2001), macroseismic data (from Andrenacci et al, 2023), and simulated coseismic displacement (Figure 10A) confirms the choice of the CF and SRF faults, respectively, as the most likely causative sources for the considered events. Figure 10C shows that it is possible to visualize the profiles of vertical coseismic displacement across CF and SRF.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Since the Messina Strait could become the site of a long bridge between Sicily and Calabria, recognizing the location and geometry of the main seismic sources in that area may be particularly useful. Several attempts to get this information have been made by studying the effects of the last two main earthquakes which affected the area, one in the northern Messina trough (M = 6.2) on 6 February 1783 (e.g., [1]) and one in the Messina sphenocasm (M = 7.1) on 28 December 1908 [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Some of the fault models indicated by the above authors for the most studied event, the 1908 shock, are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%